2022
DOI: 10.3389/fpsyg.2021.779958
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Mouthings: Evidence From a Corpus-Based Study of Russian Sign Language

Abstract: While some aspects of mouthings have been previously investigated, many topics in the use of this cross-modal contact phenomenon in sign languages remain un(der)studied, and not much is known about mouthings in Russian Sign Language (RSL), in particular. This article examines various aspects of mouthings as these are used by native RSL signers and aims to contribute new insights into the use and origin of mouthings in this sign language. Based on novel data from the online RSL Corpus alongside additional elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A further consideration is that corpus studies which collect examples of natural SL production suggest facial actions marking negation and question type may vary to a greater extent within individuals and across sign languages than might be supposed from standard descriptions of the canonical, formal structures widely cited in sign language literature (Bauer & Kyuseva, 2021;de Vos, van der Kooij & Crasborn, 2009;Johnston, van Roekel & Schembri, 2016). Our essentially null findings concerning the impact of ASD in linguistic NMMs of negation and question type 5 should be viewed in this constrained context.…”
Section: B) Understanding and Producing Linguistic Facial Actions Con...mentioning
confidence: 85%
“…A further consideration is that corpus studies which collect examples of natural SL production suggest facial actions marking negation and question type may vary to a greater extent within individuals and across sign languages than might be supposed from standard descriptions of the canonical, formal structures widely cited in sign language literature (Bauer & Kyuseva, 2021;de Vos, van der Kooij & Crasborn, 2009;Johnston, van Roekel & Schembri, 2016). Our essentially null findings concerning the impact of ASD in linguistic NMMs of negation and question type 5 should be viewed in this constrained context.…”
Section: B) Understanding and Producing Linguistic Facial Actions Con...mentioning
confidence: 85%
“…A recent paper (Bauer and Kyuseva 2022) brings up a case of mouthing in Russian Sign Language that suggests that mouthings may not be entirely influenced by spoken language, but also partly impacted by the orthography. Bauer and Kyuseva noted Russian Sign Language users typically mouth "voda" with a clear rounded mouthshape for "o" when signing their manual sign for "water," when Russian speakers actually pronounce it as "vada."…”
Section: Introduction: Mouthingsmentioning
confidence: 99%
“…Research based on different kinds of data and on different sign languages (Boyes-Braem, Sutton-Spence, 2001;Bisnath, 2022), has shown that mouthings occur more frequently than mouth gestures and both of them co-occur with the manual sign. Nevertheless, whereas mouth gestures are typically considered a part of sign language, mouthings are viewed as a sociolinguistic phenomenon due to the oral education of most deaf children (Hohenberger and Happ, 2001) and to the situation of bilingualism of most deaf adults (Boyes Braem, 2001;Bogliotti and Isel, 2021) to the interplay of the modalities of signed, spoken and written languages (Bauer, Kyuseva, 2022). Although mouthings has been considered as remnants of an oralist education (Hohenberger and Happ, 2001), not only are they very persistent in signing, but they also seem to be considered part of the language by native signers (Fontana, 2015;Bisnath, 2022) that consider "unnatural" signing without mouthings.…”
Section: Introductionmentioning
confidence: 99%